The Influence of Transformational Leadership on Job Satisfaction, Organizational Commitment and Human Resource Performance in Islamic Boarding Schools - Hery Sutanto; Yekti Utami; Aris Kusumo Diantoro (International Journal of Applied Business and International Management, 2022)
Support organizational performance requires a figure as the role model for the organization members. This research aims to investigate the influence of transformational leadership on job satisfaction, organizational commitment, and human resource performance. A survey method was used, in which primary data were obtained through questionnaires about transformational leadership, job satisfaction, organizational commitment, and human resource performance. The total number of samples is 56 respondents purposively selected based on the preset criteria. The data were descriptively and quantitatively analized by the SEM technique. The findings show that transformational leadership has a significant and positive influence on job satisfaction and organizational commitment. Job satisfaction and organizational commitment have a significant and positive influence on HR performance. Meanwhile, transformational leadership does not have a significant influence on HR performance, but it has a positive relationship.